2017
DOI: 10.18632/oncotarget.20478
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II study of aromatase inhibitors plus metformin in pre-treated postmenopausal patients with hormone receptor positive metastatic breast cancer

Abstract: BackgroundEverolimus significantly improves progression-free survival (PFS) and has been approved to use in aromatase inhibitor pretreated patients with hormone receptor positive advanced breast cancer. Metformin has been shown to inhibit mTOR pathway, with more favorable safety profile, leading to this hypothesis-generating trial to assess whether metformin enhances the efficacy of aromatase inhibitors.Methods60 postmenopausal women with hormone receptor positive locally advanced or metastatic breast cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 35 publications
5
57
0
Order By: Relevance
“…In accordance with the results from our study, a phase 2 trial of metformin 1000 mg twice daily in combination with carboplatin and pemetrexed for nonsmall cell lung cancer reported 2 grade 3 adverse events: nausea and reflux . Like other studies, there were no clinical reports of hypoglycemia or lactic acidosis in association with metformin …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with the results from our study, a phase 2 trial of metformin 1000 mg twice daily in combination with carboplatin and pemetrexed for nonsmall cell lung cancer reported 2 grade 3 adverse events: nausea and reflux . Like other studies, there were no clinical reports of hypoglycemia or lactic acidosis in association with metformin …”
Section: Discussionsupporting
confidence: 91%
“…Studies evaluating the toxicity of aromatase inhibitors in combination with metformin reported no significant difference in the rate of adverse events, but the metformin dose in those studies was relatively low at 500 mg twice daily. 39 In accordance with the results from our study, a phase 2 trial of metformin 1000 mg twice daily in combination with carboplatin and pemetrexed for nonsmall cell lung cancer reported 2 grade 3 adverse events: nausea and reflux. 40 Like other studies, there were no clinical reports of hypoglycemia or lactic acidosis in association with metformin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Gyawali et al have provided a critical review of this study, arguing lack of study power, imbalance between the two groups and other confounding factors. A study by Zhao et al also randomly assigned 60 postmenopausal women with hormone receptor positive locally advanced or metastatic breast cancer to aromatase inhibitor plus metformin or placebo. This clinical trial also failed to show an improved efficacy with the addition of metformin to endocrine therapy.…”
Section: Resultsmentioning
confidence: 99%
“…66 At present, there are only a few prospective randomised controlled trials aimed at validating the findings from observational studies, and the few that are available have failed to confirm the anticipated benefits in NSCLC, 67 pancreatic cancer 68,69 and breast cancer. 70 For example, Kordes et al 68 randomly assigned 121 patients with advanced pancreatic cancer to receive gemcitabine and erlotinib with either placebo (n = 61) or metformin (n = 60) and reported that overall survival at 6 months was 63.9% (95% CI: 51.9-75.9) in the placebo group and 56.7% (CI: 44.1-69.2) in the metformin group (P = 0.41). This may be due to the possibility that pancreatic cancer patients lack a hyperinsulinaemic state.…”
Section: Potential Use In Oncologymentioning
confidence: 99%